Characterization and genomic study of EJP2, a novel jumbo phage targeting antimicrobial resistant Escherichia coli - Jo, Dohyeong; Kim, Hyeongsoon; Lee, Yoona; Kim, Jinshil; Ryu, Sangryeol (Frontiers in Microbiology, 2023)
The emergence of antimicrobial resistance (AMR) Escherichia coli has noticeably increased in recent years worldwide and causes serious public health concerns. As alternatives to antibiotics, bacteriophages are regarded as promising antimicrobial agents. In this study, we isolated and characterized a novel jumbo phage EJP2 that specifically targets AMR E. coli strains. EJP2 belonged to the Myoviridae family with an icosahedral head (120.9 ± 2.9 nm) and a non-contractile tail (111.1 ± 0.6 nm), and contained 349,185 bp double-stranded DNA genome with 540 putative ORFs, suggesting that EJP2 could be classified as jumbo phage. The functions of genes identified in EJP2 genome were mainly related to nucleotide metabolism, DNA replication, and recombination. Comparative genomic analysis revealed that EJP2 was categorized in the group of Rak2-related virus and presented low sequence similarity at the nucleotide and amino acid level compared to other E. coli jumbo phages. EJP2 had a broad host spectrum against AMR E. coli as well as pathogenic E. coli and recognized LPS as a receptor for infection. Moreover, EJP2 treatment could remove over 80% of AMR E. coli biofilms on 96-well polystyrene, and exhibit synergistic antimicrobial activity with cefotaxime against AMR E. coli. These results suggest that jumbo phage EJP2 would be used as a potential biocontrol agent to combat the AMR issue in food processing and clinical environments.